The Plant Landscape of the “Conca d’Oro” of Palermo (NW Sicily, Italy) and Its Evolution - Gianniantonio Domina; Giulio Barone; Enrico Bajona; Emilio Di Gristina; Giuseppe Venturella; Raimondo Pardi (Plants)
The Conca d’Oro of Palermo, a plain in NW Sicily of significant historical and agricultural importance, has undergone significant landscape alterations due to agricultural strengthening and urbanization. This paper analyses the evolution of the plant landscape from early human settlements to the present by integrating historical records, cartographic analysis, and floristic surveys. Three key periods of change were identified: Roman-era deforestation for cereal cultivation, the expansion of irrigated agriculture under Arab rule, and the dominance of citrus monoculture in the 19th century. Post-World War II urban expansion led to the loss of agricultural land and natural habitats, particularly wetlands and coastal dunes. Spatial analysis revealed a drastic reduction in semi-natural areas, with agricultural land giving way to urban sprawl. Floristic studies showed the persistence of endemic plant species in fragmented natural habitats alongside the local extinction of wetlands and coastal vegetation. The Oreto River, a river with a basin that extends into the territories of the municipalities of Altofonte, Monreale, and Palermo, remains a critical biodiversity reservoir, and most other natural ecosystems have been degraded. This research provides insights into the long-term interactions between human activities and biodiversity and offers a foundation for sustainable conservation strategies in Mediterranean urban and peri-urban environments.